THE NEEDS OF CLINICAL DOMAIN LIBRARY FOR ELICITING ACCURATE CLINICAL REQUIREMENTS - Kamalrudin, Massila; Sidek, Safiah (2014)
Issues in misinterpretation of terms and miscommunication with stakeholders still persist although there are various approaches and tools available to elicit and capture accurate requirements. Specifically in healthcare domain, these issues need serious attention considering that there are myriad complex medical terminologies, unfamiliar to most requirements engineers. Further, accurate terms and words need to be captured as misinterpretations in eliciting requirements may lead to harmful consequences to human’s lives and well-being. This paper presents two preliminary studies that compare the difficulties in eliciting clinical and business requirements. Based on a survey conducted with 20 respondents, it was found that eliciting clinical functional requirements is more difficult than the business requirements. Similar findings were also drawn from interviews conducted with 5 experienced requirements engineers. They also claimed that a clinical domain library could help them to elicit accurate functional requirements. The domain library should also have e several functions that can be used to facilitate the elicitation of accurate functional requirements.